Economic Recession and its Impact on World Economy - Agarwal, Alok (2009)
In this research the researcher has given the main emphasis on how the world is going through a phase of recession and what impact it had in the global markets. The research revolves around the how the recession affects the two major economies of the world India and China. The research has been carried with the help of secondary data which includes sector wise analysis to give a brief on how each sector has been affected. The research has been done through both qualitative and quantitative data collection method. The quantitative research has been done through collecting the company’s financial statements of various companies. The main idea of the research is to know the factors which caused the recession and its impact on various sectors and how the global economies reacted towards the current period of financial crisis. The purpose of the research is to answer the question “Why we are unable to evade this global recession though we are much more technically skilled as compared to the recession that took place in the past?” The above question signifies that compared to the past the current economies of the world have a strong economic platform but why are the economies unable to perform and curb the recession. The qualitative data was collected through secondary method as well as through an interview. Recession being such a vast topic to discuss, secondary data is the best to understand the topic. Interview on the whole gives the inside information on how the industries are going through the crisis. Then the data is being completely analyzed and based upon the research the researcher has made some findings and conclusion which gives us a close idea of how the recession can be dealt with.